SURGICAL CORRECTION OF CIRCULATORY DISTURBANCE OF THE VERTEBRAL ARTERY IN TRAUMA AND DEGENERATIVE DISEASES - V. V. Shchedrenok; T. V. Zakhmatova; I. V. Zuev; O. V. Moguchaya; N. V. Topolskova; K. I. Sebelev; A. M. Malova (Вестник хирургии имени И.И. Грекова)
The article presents the results of examination and surgery of 185 patients with degenerative diseases as well as with a cervical spine trauma. The circulatory disturbance of the vertebral artery took place in all patients. A different degree of changes was observed in color duplex scanning. There were minor circulatory disturbances, course deformations (angular, C, S,Vshaped twists) and dissection of the vertebral artery. Color duplex scanning allowed estimating of local and system hemodynamic significance of extravasal influences. The strategy of treatment and volume of surgical interference were defined by the degree of circulatory disturbance in the vertebral artery.